2021
DOI: 10.1002/advs.202102451
|View full text |Cite
|
Sign up to set email alerts
|

Thiolated Nanoparticles for Biomedical Applications: Mimicking the Workhorses of Our Body

Abstract: Advances in nanotechnology have generated a broad range of nanoparticles (NPs) for numerous biomedical applications. Among the various properties of NPs are functionalities being related to thiol substructures. Numerous biological processes that are mediated by cysteine or cystine subunits of proteins representing the workhorses of the bodies can be transferred to NPs. This review focuses on the interface between thiol chemistry and NPs. Pros and cons of different techniques for thiolation of NPs are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 227 publications
(355 reference statements)
0
14
0
Order By: Relevance
“…We proposed that parts of the -SH are attacked by free radicals and oxidized to SO 2 H (sulfinic acid) or -SO 3 H (sulfonic acid) [25]. This phenomenon changed the lipophilic behavior of CNT to hydrophilic by introducing the thiol group [26].…”
Section: Characteristics Of Cmsmentioning
confidence: 99%
“…We proposed that parts of the -SH are attacked by free radicals and oxidized to SO 2 H (sulfinic acid) or -SO 3 H (sulfonic acid) [25]. This phenomenon changed the lipophilic behavior of CNT to hydrophilic by introducing the thiol group [26].…”
Section: Characteristics Of Cmsmentioning
confidence: 99%
“…The more robust net positive charge after thiolation makes NANO3-SH particularly interesting for cellular therapeutic applications, namely CRC therapy, as positively charged particles have been recurrently reported to have preferential binding activity to cell membranes and increased uptake [ 58 ]. Moreover, enhanced cellular uptake has been reported for several thiol-containing nanoparticles, which covalently bind/interact with cell surface thiol groups, increasing 100-fold the membrane transfection efficiency and endocytosis [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that thiols modulate inflammation via the NF-κB pathway. Thiol-based antioxidants have been found to mitigate the effects of oxidative stress in earlier studies. , It has been reported that there are decreased thiol/glutathione levels and thiol/disulfide imbalance in osteoporotic females. Owing to their mucoadhesive nature and cell permeation ability, thiolated polymers and nanoparticles have been employed in ophthalmic, nasal, and vaginal drug delivery systems (DDS). , Earlier studies have reported tissue regeneration and wound healing by thiolated systems. Li et al studied thiolated gelatin for wound repair and scaffold for tissue engineering; likewise, Lin et al investigated the histatin-modified chitosan hydrogel for wound healing applications .…”
Section: Introductionmentioning
confidence: 99%
“…20−22 Owing to their mucoadhesive nature and cell permeation ability, thiolated polymers and nanoparticles have been employed in ophthalmic, nasal, and vaginal drug delivery systems (DDS). 23,24 Earlier studies have reported tissue regeneration and wound healing by thiolated systems. Li et al studied thiolated gelatin for wound repair and scaffold for tissue engineering; 25 likewise, Lin et al investigated the histatin-modified chitosan hydrogel for wound healing applications.…”
Section: Introductionmentioning
confidence: 99%